Personality traits and job performance: an empirical analysis at Ibu Pejabat Bomba dan Penyelamat Pahang / Ahmad Amirul Ikshan Ahmad Tajudin - Ahmad Tajudin, Ahmad Amirul Ikshan (2015)
Personality traits influence occupational choice and are valid predictors of managerial success. The primary objective of this study was to investigate whether a relationship exists between possessing certain personality traits and employee job performance. The personality dimensions of the five-factor model of personality, Extraversion, Conscientiousness, Openness to experience, Agreeableness and Neuroticism were the focus of this study. Simple random sampling was employed and a measuring instrument distributed to respondents; 56 usable questionnaires were returned. An exploratory factor analysis was undertaken and Cronbach Alpha coefficients calculated to assess the validity and reliability of the measuring instrument. Descriptive statistics were calculated to summarise the sample data. Pearson Correlation analysis was undertaken to establish relationships between the independent variable (the five dimensions of personality) and the dependent variable, Job Performance. This findings of this study show that individuals who have high levels of the personality traits Extraversion, Conscientiousness and Agreeableness are more likely to perform better.